2022
DOI: 10.3390/machines10070548
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized VMD Method for Predicting Milling Cutter Wear Using Vibration Signal

Abstract: Tool wear has a negative impact on machining quality and efficiency. As for the nonlinear and non-stationary characteristics of vibration signals and strong background noises during the milling process, an identification method of the milling cutter wear state based on the optimized Variational Mode Decomposition (VMD) was proposed, in which the objective function is to minimize the Envelope Entropy (Ep); the various modes of the vibration signal are decomposed using the self-adaptive optimization parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Babouri et al [14] reported that the energy and the mean power of the first Intrinsic Modes Functions (IMF) of the EMD shows great potential in tool wear status recognition and the method is validated by a turning process. Chang et al [15] developed a tool wear status identification method based on the optimize VMD, and the informative IMF was selected as the sensitive IMF components, in which the relationship between features and tool wear degree was built by the Naïve Bayes classifier method. Although the signal process and feature extraction methods mention above are proven to be effective and widely used, the phase information in signals is ignored, so higher order spectrum (HOS) is applied in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Babouri et al [14] reported that the energy and the mean power of the first Intrinsic Modes Functions (IMF) of the EMD shows great potential in tool wear status recognition and the method is validated by a turning process. Chang et al [15] developed a tool wear status identification method based on the optimize VMD, and the informative IMF was selected as the sensitive IMF components, in which the relationship between features and tool wear degree was built by the Naïve Bayes classifier method. Although the signal process and feature extraction methods mention above are proven to be effective and widely used, the phase information in signals is ignored, so higher order spectrum (HOS) is applied in this paper.…”
Section: Introductionmentioning
confidence: 99%